2020
DOI: 10.1038/s41598-020-63454-1
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the sub-arc, parental magma composition for the giant Altiplano-Puna Volcanic Complex, northern Chile

Abstract: The Andean continental arc is built upon the thickest crust on Earth, whose eruption products reflect varying degrees of crustal assimilation. In order to robustly model magma evolution and assimilation at subduction zones such as the Andes, the compositions of parental magmas feeding crustal magma reservoirs need to be defined. Here we present new olivine and clinopyroxene oxygen isotope data from rare mafic volcanic rocks erupted at the margins of the giant Altiplano-Puna Magma Body (APMB) of the Altiplano-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…When magma is stored in the crust prior to eruption, its original geochemical characteristics are usually modified by fractional crystallisation, crustal assimilation, and mixing with isotopically diverse melts and fluids (e.g. [15][16][17][18][19][20] ). These processes can obscure the primary mantle sources of arc volcanism 16,21 and lead to considerable uncertainty surrounding the compositions of primary arc melts that are produced in the mantle wedge due to subduction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…When magma is stored in the crust prior to eruption, its original geochemical characteristics are usually modified by fractional crystallisation, crustal assimilation, and mixing with isotopically diverse melts and fluids (e.g. [15][16][17][18][19][20] ). These processes can obscure the primary mantle sources of arc volcanism 16,21 and lead to considerable uncertainty surrounding the compositions of primary arc melts that are produced in the mantle wedge due to subduction.…”
mentioning
confidence: 99%
“…Oxygen isotopes ratios ( 18 O/ 16 O reported in standard δnotation relative to Vienna Standard Mean Ocean Water, i.e., δ 18 O) are frequently employed to study magma genesis and evolution at arcs (e.g. 12,20,[22][23][24][25][26][27][28][29][30][31][32] ). Initially, our knowledge of the δ 18 O values of subduction zone lavas relied on analysis of pulverised whole-rocks or mineral separates of ca.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Enriched Sr and Nd isotopes, as shown in this study, have alternative explanations of inheriting from an enriched mantle source. Indeed, for large silicic systems including Yellowstone‐Snake River Plain volcanic province, Altiplano‐Puna volcanic complex, Cerro Galán, Taupo, and Toba volcanic systems, more compelling lines of evidence have indicated that the silicic magmas are mainly evolutionary products of mantle‐derived basaltic melts, with varying degrees of crustal assimilation (e.g., Folkes et al., 2011; González‐Maurel et al., 2020; McCulloch et al., 1994; Simon et al., 2014; Szymanowski et al., 2015 and this study).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, earthquakes are closely associated with tectonic activity and zones of plate subduction. Magma evolution and assimilation at the subduction zones of the Andes significantly affected the geologic setting in South America in the past [103,104]. The earthquakes usually have negative consequences and involve such hazardous events as landslides, rockfalls, and ground shaking.…”
Section: Study Areamentioning
confidence: 99%